The Effect of Using Edugame Wordwall on Students' Mathematical Representation Ability - Alna Salsabila; Ayu Tsurayya (Jurnal VARIDIKA, 2024)
The difficulty students face in comprehending problems presented through diagrams and mathematical models, coupled with the monotony experienced during mathematics lessons, has resulted in low mathematical representation skills among students. While studies indicate that Wordwall can enhance student engagement, the specific factors influencing this engagement when utilizing Wordwall remain under-explored. This study aims to assess the impact of Wordwall media on students' mathematical representation abilities and determine the extent of this influence. Adopting a quantitative research approach with experimental methods, the researchers employed a post-test-only design using cluster random sampling. Class VII-A was designated as the experimental group, while Class VII-B was the control group. Data were gathered through a post-test essay examination. Analytical techniques involved prerequisite tests (normality and homogeneity) and hypothesis testing (t-test and effect size). Results indicated a significance level of 0.008 in the t-test and an effect size of 0.685, suggesting that using Wordwall media has a moderate yet significant positive effect on students' mathematical concept representation skills. The findings reveal that incorporating Wordwall edugames in classroom instruction can enhance students' mathematical representation capabilities, foster an interactive learning environment, and improve students' self-expression. Consequently, Wordwall has been proven to elevate student engagement in learning and can effectively supplement traditional classroom instruction.